Food Security and Agrarian Policies in Tunisia, Algeria and Morocco - García, Javier Ignacio; Rodríguez, Patricia; Miranzo, Mónica (UNISCI Discussion Papers, 2014)
This article analyzes the contemporary agricultural policies in Tunisia, Algeria and Morocco. The article describes the agricultural policies of these North African countries and explains their developments and objectives in recent decades. We also examined the positive and negative results obtained in terms of modernization of the agricultural sector, increase in production and productivity, as well as its adaptation to a new context of increasing globalization and international market liberalization of agricultural products in the frame of the WTO and the agreements with the European Union. Food security appears as a fundamental objective of the agricultural policies of these Maghreb countries. In this sense, the article analyzes the different instruments and measures on supply and demand that these countries have implemented, with positive results in some cases but without reaching the target in others.
Keywords: Agricultural Policies; Food Security; Security; Tunisia; Algeria; Morocco; Maghreb.